Diseño y dimensionamiento de un sistema de energía solar para la conservación de la temperatura en cultivos (2020)
In this project, different alternatives for the electrical supply of a frost protection system in crops are compared. The previously mentioned system is based on the irrigation of water, through the use of pumps, on the crop. This process is carried out only when a meteorological frost phenomenon occurs. In first instance, a characterization of the selected study site is carried out. Subsequently, two photovoltaic systems are designed and dimensioned to supply the energy required by the irrigation pumps. The first alternative consists of an on-grid photovoltaic panel arrangement, while the second is an on-grid photovoltaic system with a battery bank integration. A technical, economic and energy balance study is carried out for each alternative, in order to determine which of the systems is optimal for this case. Additionally, the possibility of designing a water heating system based on solar thermal collectors is evaluated, which would allow the reduction of the total energy demand.--Taken from the Degree Document Format.